Odpowiedź:
zad 1
l: y = (- 1/2)x + 3
a₁ - współczynnik kierunkowy = - 1/2
b₁ - wyraz wolny = 3
k: y = a₂x + b₂
warunek prostopadłości prostych
a₁ * a₂ = - 1
a₂ = - 1/a₁ = - 1 : (- 1/2) = 1 * 2 = 2
Prosta k ma postać:
k: y = a₂x + b₂ = 2x + b₂ , A = (2 , - 1 )
- 1 = 2 * 2 + b₂
- 1 = 4 + b₂
b₂ = - 1 - 4 = - 5
k: y = 2x - 5
zad 2
l: y = 3x + 2
a₁ = 3 , b₁ = 2
Warunek równoległości prostych
a₁ = a₂
prosta k ma postać
k: y = a₂x + b₂ = 3x + b₂ , A = (- 1 , 2 )
2 = 3 * (- 1) + b₂
2 = - 3 + b₂
b₂ = 2 + 3 = 5
k: y = 3x + 5
zad 3
A = (- 2 , 4 ) , S = ( - 6 , - 8 ) , B = (xb , yb)
xa = - 2 , xs = - 6 , ya = 4 , ys = - 8
xs = (xa + xb)/2
2 * xs = xa + xb
xb = 2 * xs - xa = 2 * (- 6) + 2 = - 12 + 2 = - 10
ys = (ya + yb)/2
2 * ys = ya + yb
yb = 2 * ys - ya = 2 * (- 8) - 4 = - 16 - 4 = - 20
B = (- 10 , - 20)